Polygyny and intimate partner violence among married women: Sub-national estimates from a cross-sectional study in the Democratic Republic of the Congo. - Zacharie Tsala Dimbuene; Bright Opoku Ahinkorah; Dickson Abanimi Amugsi (PLOS Global Public Health)
Intimate partner violence (IPV) is a global issue with several social and health consequences. Global estimates indicate that one-third of women have experienced lifetime IPV. In 2013, sub-Saharan Africa recorded the highest rates of IPV. Furthermore, previous research showed that polygyny is positively associated with IPV. This study examined associations between polygyny and IPV in Democratic Republic of the Congo (DRC) with a special attention to geographical variations. The paper used a subsample of 3,749 married women from 2013-2014 Demographic and Health Survey (DHS) in the DRC. Univariate and multivariable logistic regression was conducted to test statistical significance between polygyny and IPV and p < 0.05 was considered statistically significant. Findings showed spatial variations for polygyny and the three types of IPV. Overall, 19.0% of married women were in polygynous unions. This percentage ranged from 5.7% in North Kivu to 29.4% in Kasai occidental. In the last 12 months, 28.6%, 27.8%, and 19.6% of married women reported physical, emotional, and sexual violence, respectively, while 43.2% reported any form of IPV. IPV rates ranged from 18.1% in Kongo central to 58.3% in Kasai occidental. Net of controls, women in polygynous unions living Bandundu [AOR = 2.16, 95%CI = 1.38-3.38], Katanga [AOR = 1.78, 95%CI = 1.09-2.89], North Kivu [AOR = 6.22, 95%CI = 1.67-23.22], and South Kivu [AOR = 2.79, 95%CI = 1.03-7.54] had higher rates of IPV than their counterparts in monogamous unions. Spatial analyses showed that Kasai Occidental had the highest rates of IPV. Overall, being in polygynous increased significantly the odds of IPV. Programmatically, policymakers and stakeholders need to devise more effective policies and IPV interventions targeting polygynous families in DRC to achieve Sustainable Development Goals (SDG) 5.2, that aimed to eliminate all forms of violence against women and girls by 2030.